Perancangan Prototipe Sistem Pemesanan Makanan dan Minuman Menggunakan Mobile Device - Sandy Kosasi (JATISI (Jurnal Teknik Informatika dan Sistem Informasi), 2015)
The purpose of this research resulted in a more efficient and effective prototype system application of ordering food and beverage through mobile devices in enjoying various types of food and beverage, and chances to increase the personalization relationship with online visitors or customers of a restaurant. This research is in form of a survey and uses research & development (R & D) method. The design of prototipe system applications use an agile model with extreme programming method, and the modeling of the system uses Unified Modeling Language (UML). This application system has three main interfaces of waiter (waitress), kitchen (chefs) and cashier (cashier). These three modules interconnected through the database integration processes. The architectural describe the software at the web server and its clients. The web server design uses apache software supported by PHP script with MySQL database.